2020
DOI: 10.3390/biomedicines8050124
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Biological Processes and Nitrergic Signaling in Mouse Brain

Abstract: Nitric oxide (NO) represents an important signaling molecule which modulates the functions of different organs, including the brain. S-nitrosylation (SNO), a post-translational modification that involves the binding of the NO group to a cysteine residue, is a key mechanism of nitrergic signaling. Most of the experimental studies are carried out on male animals. However, significant differences exist between males and females in the signaling mechanisms. To investigate the sex differences in the SNO-based regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 101 publications
2
14
0
Order By: Relevance
“…These results join our recent reports in showing that the mechanisms mediating extinction in adult and juvenile animals may be distinctive 6 8 , 29 . The present findings provide strong evidence of sex difference, even before sexual maturation, in many biological processes and signaling and point to substantial differences between males and females 76 . This will open future research directions on sex differences in neurological and psychiatric disorders 76 , 77 .…”
Section: Discussionsupporting
confidence: 55%
“…These results join our recent reports in showing that the mechanisms mediating extinction in adult and juvenile animals may be distinctive 6 8 , 29 . The present findings provide strong evidence of sex difference, even before sexual maturation, in many biological processes and signaling and point to substantial differences between males and females 76 . This will open future research directions on sex differences in neurological and psychiatric disorders 76 , 77 .…”
Section: Discussionsupporting
confidence: 55%
“…Between our study and that of Sowers et al (2019), which was also conducted in C57BL/6J mice but in hippocampi, there were several proteins that were differentially regulated in the same direction by sex (Alb, Camk2a, Cpne6, and Synpr) and some proteins that were differentially regulated but in opposite directions (Anxa6, L1cam, Scg2, and Vat1l). Other studies examining sex differences in experimentally naïve rodents (i.e., under "baseline" conditions), focused on specific neuronal compartments such as the synapse (Distler et al, 2020), microglia (Guneykaya et al, 2018), mitochondria in microvasculature (Cikic et al, 2021), or a specific type of protein modification (Khaliulin et al, 2020). Thus, the current study demonstrating a significant degree of sex difference in the mesolimbic proteome at baseline is an important contribution to broadening the understanding of baseline sex differences in the mouse brain.…”
Section: Discussionmentioning
confidence: 79%
“…One important aspect of the research on brain sexual di-morphism was finding the changes in S-nitrosylation (S-NO) of mouse cortical proteins. Mass spectrometry analysis revealed that female mice showed elevated levels of S-NO proteins involved in synaptic processes, while males exhibited higher enrichment of the S-NO-dependent cytoskeletal pathways [50]. S-NO is engaged in a variety of cellular processes and, importantly, this PTM appears to compete with S-PALM for cysteine residues in proteins [51,52].…”
Section: Discussionmentioning
confidence: 98%